Palladium-complex-promoted asymmetric Diels-Alder reaction: Stereoselective synthesis of a new sulfinyl-substituted phosphine ligand containing three carbon, one phosphorus and one sulfur stereogenic centres - Siah, S.-Y. (2014)
10.1039/C39950001747